Anti-oxidant, hypoglycemic and anti-hyperglycemic properties of Syzygium calophyllifolium (Bangladesh Journal of Pharmacology, 2015)
The article discusses anti-oxidant oral glucose tolerance and anti-hyperglycemic potentials of Syzygium calophyllifolium. Extracts from successive solvent extraction were tested for the total phenolic, tannin, flavonoid content and free radical scavenging property using DPPH, ABTS+, phosphomolyb-denum, FRAP, superoxide and metal chelating assays. Ethyl acetate extract of bark responded well against DPPH (IC50 4.13), ABTS+ (36832.29 µM TE/ g extract),phosphomolybdenum (100.4 g AAE/100g extract), superoxide and metal ion radicals. The methanol extract of bark was also found as an effective radical scavenger. The leaf methanol extract also showed significant anti-oxidant ability. The bark methanol extract could potentially reduce the blood glucose level in glucose loaded and diabetic rats. The immense anti-oxidant potential of S. calophyllifolium leaf and bark extracts could be taken as a good source of natural anti-oxidant supplement in food to defend oxidative stress related disorders like diabetes.